Detection and mapping of homologous, repeated and amplified DNA sequences by DNA renaturation in agarose gels. - Roninson, I B (Nucleic Acids Res, 1983)
A new molecular hybridization approach to the analysis of complex genomes has been developed. Tracer and driver DNAs were digested with the same restriction enzyme(s), and tracer DNA was labeled with 32P using T4 DNA polymerase. Tracer DNA was mixed with an excess amount of driver, and the mixture was electrophoresed in an agarose gel. Following electrophoresis, DNA was alkali-denatured in situ and allowed to reanneal in the gel, so that tracer DNA fragments could hybridize to the driver only when homologous driver DNA sequences were present at the same place in the gel, i.e. within a restriction fragment of the same size. After reannealing, unhybridized single-stranded DNA was digested in situ with S1 nuclease. The hybridized tracer DNA was detected by autoradiography. The general applicability of this technique was demonstrated in the following experiments. The common EcoRI restriction fragments were identified in the genomes of E. coli and four other species of bacteria. Two of these fragments are conserved in all Enterobacteriaceae. In other experiments, repeated EcoRI fragments of eukaryotic DNA were visualized as bands of various intensity after reassociation of a total genomic restriction digest in the gel. The situation of gene amplification was modeled by the addition of varying amounts of lambda phage DNA to eukaryotic DNA prior to restriction enzyme digestion. Restriction fragments of lambda DNA were detectable at a ratio of 15 copies per chicken genome and 30 copies per human genome. This approach was used to detect amplified DNA fragments in methotrexate (MTX)-resistant mouse cells and to identify commonly amplified fragments in two independently derived MTX-resistant lines. IMAGES: